Th17 polarization of memory Th cells in early arthritis: the vasoactive intestinal peptide effect. Issue 2 (8th May 2015) - Jimeno, Rebeca; Leceta, Javier; Garín, Marina; Ortiz, Ana M; Mellado, Mario; Rodríguez-Frade, Jose Miguel; Martínez, Carmen; Pérez-García, Selene; Gomariz, Rosa P; Juarranz, Yasmina
Abstract : Th17 cells from eRA patients are prone to expand to a pathological cell population under Th17-polarizing conditions where VIP prevents their pathogenesis. Abstract: Several studies in humans indicate the implication of Th 17 cells in RA. Therapies targeting their pathogenicity, as well as their plasticity to the Th 17/1 phenotype, could ameliorate the progression of the pathology. The neuroendocrine environment has a major impact on the differentiation of lymphoid cells. VIP is present in the microenvironment of the joint, and its known therapeutic effects are supported by several studies on RA. We examine the ability of VIP to modulate the differentiation of Th 17 cells. Peripheral blood CD4 + CD45RO + T cells from HD and eRA patients were expanded under Th 17-polarizing conditions in the presence of TGF-β. After 7 days, the higher IL-17A, IL-21, and IL-9 levels and lower IL-22 levels indicate the nonpathogenic profile for Th 17 cells in HD. In contrast, Th 17 cells from eRA patients produced significantly more IL-22 and IFN-γ, and these cells show a more Th 17/1 profile, indicating a pathogenic phenotype. Interestingly, when VIP was present in the Th 17 conditioned medium, increased levels of IL-10 and IL-9 were detected in HD and eRA patients. VIP also reduced the levels of IL-22 in eRA patients. These data suggest that VIP reduces the pathogenic profile of the Th 17-polarized cells. This effect was accompanied by an increased in the Treg /Th 17 profile, as shown by the increase levels of Foxp3. In conclusion, this report addresses a novel and interesting question on the effect of VIP on human Th 17 cells and adds clinical relevance by analyzing, in parallel, HD and eRA patients.